Axially Chiral 1, 1'‐Binaphthyl‐2‐Carboxylic Acid (BINA‐Cox) as Ligands for Titanium‐Catalyzed Asymmetric Hydroalkoxylation. Issue 14 (1st April 2020) - Helmbrecht, Sebastian L.; Schlüter, Johannes; Blazejak, Max; Hintermann, Lukas
Abstract : Axially chiral, enantiopure 1, 1'‐binaphthyl‐2‐carboxylic acids (BINA‐Cox) have recently been introduced as chiral ligands for transition metal catalysis. Together with equimolar, co‐catalytic amounts of Ti(O i Pr)4 and water they form an in situ catalyst that performs the asymmetric catalytic hydroalkoxylation of 2‐allylphenols to 2‐methylcoumarans at high temperature (240 °C, microwave heating). The synthesis of reference ligand 2'‐MeO‐BINA‐Cox (L1 ) has been optimized and performed at molar scale. Synthetic routes have been developed to access a variety of substituted BINA‐Cox ligands (>30 examples), which have been tested for ligand effects on the reference asymmetric cyclization of 2‐allylphenol. The substrate range of asymmetric catalytic hydroalkoxylation has been explored through systematic substrate structure variations to define scope and limitations of the titanium‐catalyzed process. The new substrates 2‐(1‐vinylcycloalkyl)phenols (1j, 1k ), 2‐(2‐vinylphenyl)propan‐2‐ol (1t ), and 2'‐vinyl‐[1, 1'‐biphenyl]‐2‐ol (1u ) are shown to undergo asymmetric catalytic cyclization to benzodihydrofurans and benzo[ c ]chromene, respectively. Abstract : By mixing titanium isopropoxide, water, and 1, 1'‐biaryl‐2‐carboxylic acids, a catalyst for the asymmetric addition of phenolic hydroxyl to non‐activated alkene at high temperature (240 °C) is formed. This work systematically develops scalable syntheses of variably decorated, enantiopure 1, 1'‐biaryl‐2'‐carboxylic acids, which are then tested as steering ligands in intramolecular asymmetric catalytic hydroalkoxylation reactions.